Computer usage among bank employees in Kuching - Juliana @ Julie, Johari (Faculty of Computer Science and Information Technology, 2000)
The purpose of this study is to determine the level of computer use and the attitude towards computer among bank employees. Relationship between level of computer skills and selected demographic characteristics of the bank employees were also investigated. This study also looked at the relationship between attitude towards computers, namely confidence, anxiety, competency, and enjoyment with computer use for banking purposes among bank employees.